Controlled-release fertilizers increase sunflower yield by regulating soil nitrogen, photosynthesis, and root structure in arid regions - Ren, Wenhao; Li, Xianyue; Liu, Tingxi; Chen, Ning; Xin, Maoxin; Qi, Qian; Liu, Bin (Frontiers in Plant Science, 2026)
Background and aimsIn arid irrigated systems, nitrogen supply often mismatches crop demand. This study assessed whether controlled-release fertilizers (CRF) better synchronizes nitrogen supply with sunflower demand than traditional nitrogen fertilizer (TNF), by comparing field treatments, quantified soil–root–plant responses, and identified the CRF rate that maximizes yields and nitrogen use efficiency (NUE).MethodsA three-year field experiment (2019–2021) was conducted in the Hetao Irrigation District, Bayannur, Inner Mongolia, China, using sunflower cultivar SH361. Treatments compared CRF and TNF at 135, 225, and 315 kg N/ha. Measurements included soil nitrate (0–100 cm), root traits (surface area density, dry weight), root sap production and sap nitrate, relative chlorophyll values, net photosynthetic rate, plant nitrogen uptake, and yield.ResultsRelative to TNF, CRF significantly improved soil–root–plant N dynamics, increasing sunflower yield by 23.83%, plant NU by 8.17%, and NUE by 14.46%. CRF225 achieved the highest NUE while maintaining a yield statistically equivalent to CRF315, indicating that additional N input beyond 225 kg/ha conferred no yield benefit. Enhanced yield under CRF was strongly associated with higher soil nitrate availability, greater root activity, and increased photosynthesis.ConclusionCRF improved nitrogen synchrony, yield, and NUE under arid irrigation. The 225 kg N/ha CRF rate provided the most favorable yield–efficiency balance, offering a practical management strategy for sustainable production in water-limited regions. By quantitatively linking CRF to soil–root–plant nitrogen coordination, this study advances understanding of nitrogen optimization in arid irrigated systems.